Numerical Analysis of Baffle Cut on Shell Side Heat Exchanger Performance with Inclined Baffles. Issue 13 (27th August 2018) - Kumaresan, Govindaraj; Santosh, Ravichandran; Duraisamy, Ponnukutti; Venkatesan, Ramar; Kumar, Nathamani Satheesh
ABSTRACT: In this work, an attempt has been made to decrease the pressure drop and to increase the heat transfer rate in a shell and tube heat exchanger (STHX) by tilting the baffle angle and by varying the baffle cut. The process of solving the simulation includes modeling, meshing, and analyzing the geometry of the STHX by using Pro-E, hypermesh, and computational fluid dynamics package of ANSYS Fluent, respectively. The objective of this study is to find a suitable baffle inclination and baffle cut for the efficient performance of the STHX. The baffle inclinations of 25°, 30°, 35°, and 40° were considered for three different baffle cuts of 25%, 30%, and 35% of shell inside diameter and the results were compared with segmental baffle of inclination angle 0°. The shell side flow with different inclination angles and baffle cuts results in a significant variation in heat transfer rate and pressure drop in the STHX. The results provide a clear idea that the heat transfer rate is maximum in inclined baffle heat exchanger compared to that of segmental baffle heat exchanger. Further it is found that the STHX with the configuration of 35º baffle inclination angle and baffle cut of 30% of shell inside diameter provides higher heat transfer rate with minimum pressure drop compared to all other configurations.